S20: Advancing Knowledge on Equitable Physical Activity Policy Implementation: Learnings From the IMPAQT Consortium (Baltic Journal of Sport and Health Sciences, 2026)
The growing burden of non-communicable diseases demands systemic solutions that promote population-level physical activity (PA) and address longstanding health inequities. Public policies have the potential to be one such solution. IMPAQT, which stands for ‘IMproving Physical Activity policies and their impact on health eQuiTy’ aims to improve health equity in and through PA by developing and implementing the Physical Activity Environment Policy Index (PA-EPI) across six diverse countries. For more details see: www.ul.ie/research/impaqt. This symposium explores key dimensions of this work, from reviewing the scientific evidence to strategies for ensuring equity throughout the policy assessment process and its application.Presentation one provides results from a literature review assessing the evidence for the effect of public PA policy on health equity. Presentation two introduces an equity module developed for the PA-EPI, designed to embed systematic equity considerations across its 45 policy indicators. Presentation three offers guidance on the equitable recruitment of stakeholder councils as part of the PA-EPI process. The PA-EPI council’s role is to assess the evidence of policy implementation for each country and provide recommendations to address critical implementation gaps. IMPAQT has been designed to maximise inclusive representation in policy evaluation. Presentation four will share information about the development of a curated set of Best Practice Exemplars of policy implementation, offering globally sourced policy examples aligned with PA-EPI benchmarks.Together, these contributions showcase how policy evaluation, co-creation, and benchmarking, grounded in evidence and equity, can guide more effective, inclusive, and systemically sustainable actions to increase physical activity and reduce health disparities across populations. This symposium will share learning from the research team across seven European countries with an emphasis on discussion, reflection, and self-evaluation in relation to the future of physical activity policy.